Live cell imaging of single RNA molecules with fluorogenic Mango II arrays - Adam D. Cawte (Nature Portfolio, 2020)
Fluorogenic RNA aptamers have been used for RNA imaging, but folding and fluorescence stability often limited their use in high resolution applications. Here the authors present an array of stably folding Mango II aptamers for imaging of coding and non-coding RNAs at single-molecule resolution, in both live and fixed cells.